(untitled) (Docentes 2.0 Journal, 2022)
Microcurricular planning is an essential tool that strengthens the work methodology applied by teachers in educational institutions of initial education; therefore, it is necessary that this planning be flexible and meet the five moments: diagnosis, purpose, selection of strategies, tools, and assessment, as stipulated in the national curriculum. The objective of this article was to determine if the micro-curricular planning developed by teachers contributes to learning achievements at the initial education level. The positivist paradigm used the deductive method with a quantitative approach, descriptive-exploratory type, and non-experimental design. It was developed with a non-probabilistic convenience sample of 17 initial education teachers in an educational institution in the canton of Santa Elena, province of Santa Elena-Ecuador. For data collection, a survey was designed with its respective Likert scale and applied to the study subjects to evaluate the effectiveness of micro-curricular planning. The instrument’s reliability was obtained with the statistical program SPSS through the Cronbach coefficient that reflected a value of 0.969. As a result, it was detected that teachers know the phases of micro-curricular planning; however, they show difficulties when carrying out these phases in practice. It is concluded that when this tool is always applied appropriately, it benefits the learning acquisition of children at the initial level.